BIG DATA: HOW CAN INFORMATION TECHNOLOGIES HELP THE STATISTICS SERVICE TO INCREASE EFFICIENCY OF CALCULATION OF THE CONSUMER PRICE INDEX - A. Mikhajlova (Publishing House of the State University of Management, 2018)
The results of the study of the application of the Big Data technologies in calculating the consumer price index (CPI) has been presented. The object of the study is the state institution «Federal State Statistics Service» (ROSSTAT), the subject of the study - the process of calculating the CPI based on data coming to the ROSSTAT. The purpose of the study is to develop recommendations on the application of Big Data in the statistics of consumer prices. The business and information technology (IT) architecture of the ROSSTAT were developed with the help of the step-by-step instruction for the development of architecture TOGAF (The Open Group Architecture Framework).